"Медвежья вечерка" у хантов р. Демьянка: опыт наблюдения 2015 г. - Telegina, L. A.; Телегина, Л. А. (Издательство Тюменского государственного университета, 2016)
The paper deals with a detailed description of the traditional Bear festival of the Eastern Khanty of the Demyanka river valley, which the author managed to visit 13-15 April 2015 (Yarsino village, Uvatsky district of Tyumen region). The local Khanty are descendants of the migrants from the neighbor basin of the Bolshoy Yugan river, who moved to the new place of living in the 1940s. The modern inhabitants of the Demyanka river are some of the few representatives of the Khanty, who retained the traditional ritual of the Bear festival to this day. The observed festival was devoted to a male bear and therefore had to be composed of 5 days. However, due to the presence of our visiting group those 5 days were symbolically realized in 3 days. The presented description of the ceremony shows that the tradition of the Bear festival is well preserved by the Demyanka Khanty. It must be particularly noted that some characteristics of the ritual have a pronounced ecological context. A large number of performed songs and scenes, including both scripted and improvised, indicates a significant amount of the saved ritual, the analysis and studying of which will continue in the coming years. Исследуется культ медведя у хантов р. Демьянка.